Prediction and analysis of trends in the nutritional status of children under 5 years in Iran: reanalysis of the results of national surveys conducted between 1998 and 2020 - Ghodsi, Delaram; Rasekhi, Hamid; Yari, Zahra; Roustaee, Roshanak; Nikooyeh, Bahereh; Faramarzi, Ayoub; Eini-Zinab, Hassan; Neyestani, Tirang R. (Frontiers in Nutrition, 2023)
Background and aim Malnutrition is a major public health problem, especially in developing countries. The aim of this study was to analyze the trend in malnutrition among children under 5 years of age in Iran over recent decades and to estimate malnutrition status for 2020. Methods This study took the form of a secondary analysis of the reports and data from three cross-sectional national surveys on children's nutritional status conducted between 1998 and 2017. Anthropometric indices, including markers of underweight, wasting, stunting, overweight, and obesity, were used as indicators of the nutritional status of children under 5 years. Malnutrition indicators are reported separately based on regional food security status. Linear mixed-effects modeling was used to predict the status of malnutrition indicators for 2020. Results The results of this study indicated a downward trend in the prevalence of stunting, underweight, and wasting, from 15.4 to 4.8%, 10.9 to 4.3%, and 4.9 to 4.3%, respectively, between 1998 and 2017. The proportion of children at risk of overweight and prevalence of childhood overweight/obesity showed a downward trend between 2010 and 2017, from 3.73 to 3.02% and from 12.1 to 10.3%, respectively. However, the trend varied between different provinces. Estimates of the prevalence of malnutrition in 2020 also indicated a decrease in the prevalence of all indicators among children. Conclusion Despite the decreasing trend in malnutrition over the past three decades, the prevalence of stunting, underweight, and wasting is still high in food-insecure provinces. Moreover, following the COVID-19 pandemic and its economic consequences, an increase in the prevalence of malnutrition, especially in food-insecure provinces, is plausible.